Management of Wetlands and Livelihood Opportunities in Kinawataka Wetland, Kampala-Uganda - Kakuba, Sultan Juma; Kanyamurwa, John Mary (Environmental Challenges, 2021)
Wetlands are globally recognized as ecosystems that provide livelihood opportunities in aptly structured management contexts. Many wetlands, particularly those in urban Uganda are, however, getting degraded through infilling, construction, extraction, agricultural and industrial production despite the existing resource management regime. The purpose of this study was to analyze the gap between wetland management practices and extent of sustainable harnessing of livelihood opportunities. Therefore, this study contributes to an understanding of wetland management functions in relation to sustainable livelihoods. Cross-sectional qualitative and quantitative data were collected to investigate the stated relationships. The study established a positive but insignificant relationship between planning function and sustainable livelihood opportunities. Further, the study found a negative significant relationship between implementation and sustainable production. Finally, findings revealed that there was a connection between the control function and sustainable opportunities. The study recommends inclusive management functions to achieve sustainable wetland livelihood opportunities.
Keywords: Management of Wetlands and Livelihood Opportunities in Kinawataka Wetland, Kampala-Uganda